Influence of Cutting Parameters on Cylindricity Deviation by Centerless Grinding - Stancekova, Dana; Martikan, Pavol; Svobodova, Jaroslava; Janota, Miroslav; Kratochvil, Jiri (Manufacturing Technology Journal, 2018)
Grinding is one of the oldest ways of material machining operations. The requirement to produce fast and cost-effective parts in large quantities has classified the metal grinding in the engineering industry for major machining operation. The complexity of the abrasive process and the amount of abrasive tool parameters have considerable problems in the theoretical and experimental study of this process, which is machining with undefined cutting-edge tool. The submitted verifications are aimed at intensifying grinding without medium stress due to the cylindrical deviation. Also, these verifications are aimed to the adjustment of centreless grinding conditions for a given value of the geometric deviation of the shaft and the influence of the abrasive conditions on a given cylindricity deviation.
Keywords: Centreless grinding; Deviation of cylindrical; Speed